Proposing Islamic core values: firming up the principles of corporate governance in Islamic financial institutions / Daing Maruak Sadek ... [et al.] - Sadek, Daing Maruak; Anuar, Azyyati; Wan Omar, Wan Nor Faaizah (2018)
The concept of corporate governance in Islam refers to establish an organizational planning on how a corporation is directed, managed, governed and controlled. This provides the governance structure through which all stakeholders interests are protected, the company’s objective is achieved and the principles of Sharia’ have complied with. Since the establishment of the Islamic finance industry about 40 years ago, the issue of corporate governance has been constantly deliberated to ensure Islamic Financial Institutions (IFIs) serve the interests of various parties like the depositors, investment account holders, stockholders and the other general stakeholders. The difference between IFIs and the other organization like conventional banks and others lies in the objective of establishing IFIs which is to carry out business activities that are consistent with Sharia’. However, there are some issues still actively debated among academician, especially controversial about the efficiency of corporate governance and corporate accountability. Furthermore, it is argued the establishment of Guidelines on corporate governance might not be sufficient whereby there is a necessity to intensely reassess of corporate governance principles of IFIs in order to tackle the problem of governance weaknesses. Therefore, it is required for this study to bridge the gap between conventional and Islamic by proposing Islamic core values based on Al-Quran and Sunnah in order to firm up the principles of corporate governance in Islamic Financial Institutions.